1981
DOI: 10.3758/bf03209787
|View full text |Cite
|
Sign up to set email alerts
|

Contextual generality of roosttime restlessness in captive American robins (Turdus migratorius)

Abstract: A series of experiments with captive American robins examined factors affecting roosttime restlessness, that is, the burst of locomotor activity that appears at dusk and is thought to be a correlate of the communal roosting habit of this species. First, the restlessness occurred earlier on cloudy days than on sunny ones, suggesting the importance of illumination level in initiating the activity burst. Second, in studies on social effects, the restlessness was greater when robins were totally isolated than when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous research with robins has demonstrated that the visible presence of a quiet observer does not change the overall pattern of circadian activity in that species (Eiserer, 1981).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research with robins has demonstrated that the visible presence of a quiet observer does not change the overall pattern of circadian activity in that species (Eiserer, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon is reflected also in the daily activity pattern of captive robins under conditions of natural illumination (Eiserer, 1979(Eiserer, , 1981. In particular, moderately high activity levels in the early morning gradually decline as the day progresses, but a brief period of high activity invariably occurs at dusk, before the birds settle down for the night (Eiserer, 1979;Palmer, 1970).…”
mentioning
confidence: 99%